IMPACT OF MANAGERIAL OWNERSHIP, COMPANY SIZE AND CAPITAL STRUCTURE ON COMPANY VALUE THROUGH PROFITABILITY IN COMPANY SECTORS PROPERTY, REAL ESTATE AND BUILDING CONSTRUCTION LISTED ON INDONESIA STOCK EXCHANGE PERIOD 2019–2021 - Jesslin Yosanti; Aremi Evanta Br Tarigan; Teng Sauh Hwee (Економіка та суспільство, 2023)
The research aims to test and analyze the influence of managerial ownership, the size of the company, and the capital structure on the value of a company with profitability as an intervening variable. In this study, the researchers used external data obtained from the Indonesian Stock Exchange, which processed data of the Company's property, real estate and building sectors listed during the period 2019-2021. Sampling using purposive sampling, where the population is 32 companies so in a three-year period of 96. The data analysis process is statistically tested using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach and the processing medium is SmartPLS 3.2.9. The value of the company is still a factor that investors pay attention to the ratio used is Price to Book Value, which is a simple valuation method and can be used by investors to analyze whether the price of a stock is undervalued or overvalued. The sectors used in property, real estate and building construction have brilliant prospects and are supported by the government and the valuation of corporations belonging to them has a significant influence on the state. The sector of real estate, building and construction has a relatively stable PBV ratio to a relative stable share price, so the researchers are looking at other financial ratios that are related to profitability and can affect the value of the company. The results show that capital structure and profitability don’t effect the company, but managerial ownership and the size of a company have a negative effect on the company's value. Profitability cannot mediate the effect of managerial ownership, company size and capital structure on the company's value. With this research, the Company can increase the value of the Company and strive to profitability that benefits the investor or the company itself, then able to perform tasks or responsibilities for decision-making with stability and vigilance. Meanwhile, companies are able to evaluate the factors that can affect the value of the company and consider which items need to be upgraded. The research focuses on managerial ownership, company size, capital structure, company value and profitability. It's done because we're so interested in this phenomenon. Company value items are like mirrors that can reflect the company's market assessment and help investors determine the viability of the company to invest in.